Charting the Digital Experience: A Study of What Drives Customer Joy Online - Mas’adah, Ninik (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The development of the business and marketing world is influenced by the increasing development of technology and information. The internet is not only used as a website but also as a source of information, buying and selling products, and providing services online in e-commerce. E-commerce businesses in Indonesia are influential and able to change various consumer behaviors. One of the many behaviors is going from buying things in malls and stores every day to buying online now. This study aims to examine the importance of price perception, service quality perception, convenience perception, and usability perception for e-commerce satisfaction. This study involved 2,500 students of the University of Muhammadiyah Lamongan from semesters 2 to 6. The sample used was 155 students who had met the criteria by applying the purposive sampling technique. The analysis method used SPSS 25. The information for this study was collected through filling out a questionnaire by students of the University of Muhammadiyah Lamongan using Google Forms, which was then disseminated through the social media platform WhatsApp. The results of this study are that the perception of price, the perception of service quality, and the perception of convenience do not have a significant impact on client happiness, while the perception of usability has an effect on consumer satisfaction.